The worse we feel, the more intensively we need to stick together: a qualitative study of couples’ emotional co-regulation of the challenge of multimorbidity - Horn, Andrea B.; Zimmerli, Lukas; Maercker, Andreas; Holzer, Barbara M. (Frontiers in Psychology, 2023)
Being faced with multimorbidity (i.e., being diagnosed with at least two chronic conditions), is not only demanding in terms of following complicated medical regimes and changing health behaviors. The changes and threats involved also provoke emotional responses in the patients but also in their romantic partners. This study aims at exploring the ways of emotional co-regulation that couples facing multimorbidity express when interviewed together. N = 15 opposite sex couples with one multimorbid patient after an acute health crisis that led to hospitalization were asked in a semi-structured interview about how they found ways to deal with the health situation, what they would recommend to other couples in a similar situation, and how they regulated their emotional responses. Interviews were analyzed qualitatively following open, axial, and selective coding, as in the grounded theory framework. Emerging categories from the romantic partners’ and the patients’ utterances revealed three main categories: First, overlapping cognitive appraisals about the situation (from fighting spirit to fatalism) and we-ness (construing the couple self as a unit) emerged as higher order factor from the utterances. Second, relationship-related strategies including strategies aimed at maintaining high relationship quality in spite of the asymmetric situation like strengthening the common ground and balancing autonomy and equity in the couple were often mentioned. Third, some couples mentioned how they benefit from individual strategies that involve fostering individual resources of the partners outside the couple relationship (such as cultivating relationships with grandchildren or going outdoors to nature). Results underline the importance of a dyadic perspective not only on coping with disease but also on regulating the emotional responses to this shared challenging situation. The utterances of the couples were in line with earlier conceptualizations of interpersonal emotion regulation and dyadic perspectives on we-disease. They broaden the view by integrating the interplay between individual and interpersonal regulation strategies and underline the importance of balancing individual and relational resources when supporting couples faced with chronic diseases.